Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's carefully go through the process of finding [tex]\((h - f)(x)\)[/tex] and [tex]\(m(x) = (g - j)(x)\)[/tex], and then evaluating [tex]\(m(3)\)[/tex].
### Find [tex]\((h - f)(x)\)[/tex]:
Given:
- [tex]\( f(x) = x + 5 \)[/tex]
- [tex]\( h(x) = 2x - 3 \)[/tex]
Step-by-step process:
1. Write the expression for [tex]\((h - f)(x)\)[/tex]:
[tex]\[ (h - f)(x) = h(x) - f(x) = (2x - 3) - (x + 5) \][/tex]
2. Distribute the subtraction to each term:
[tex]\[ (h - f)(x) = 2x - 3 - x - 5 \][/tex]
3. Combine like terms:
[tex]\[ 2x - x - 3 - 5 = x - 8 \][/tex]
So, [tex]\((h - f)(x) = x - 8\)[/tex].
### Find [tex]\(m(x) = (g - j)(x)\)[/tex]:
Given:
- [tex]\( g(x) = x^2 + 6x + 5 \)[/tex]
- [tex]\( j(x) = -4x \)[/tex]
Step-by-step process:
1. Write the expression for [tex]\((g - j)(x)\)[/tex]:
[tex]\[ m(x) = (g - j)(x) = g(x) - j(x) = (x^2 + 6x + 5) - (-4x) \][/tex]
2. Distribute the subtraction to each term, noting that subtracting a negative is the same as adding:
[tex]\[ m(x) = x^2 + 6x + 5 + 4x \][/tex]
3. Combine like terms:
[tex]\[ x^2 + 6x + 4x + 5 = x^2 + 10x + 5 \][/tex]
So, [tex]\(m(x) = x^2 + 10x + 5\)[/tex].
### Evaluate [tex]\(m(3)\)[/tex]:
Given [tex]\(m(x) = x^2 + 10x + 5\)[/tex]:
Substitute [tex]\(x = 3\)[/tex] into the function:
[tex]\[ m(3) = (3)^2 + 10(3) + 5 \][/tex]
[tex]\[ m(3) = 9 + 30 + 5 \][/tex]
[tex]\[ m(3) = 44 \][/tex]
Therefore, [tex]\(m(3) = 44\)[/tex].
### Find [tex]\((h - f)(x)\)[/tex]:
Given:
- [tex]\( f(x) = x + 5 \)[/tex]
- [tex]\( h(x) = 2x - 3 \)[/tex]
Step-by-step process:
1. Write the expression for [tex]\((h - f)(x)\)[/tex]:
[tex]\[ (h - f)(x) = h(x) - f(x) = (2x - 3) - (x + 5) \][/tex]
2. Distribute the subtraction to each term:
[tex]\[ (h - f)(x) = 2x - 3 - x - 5 \][/tex]
3. Combine like terms:
[tex]\[ 2x - x - 3 - 5 = x - 8 \][/tex]
So, [tex]\((h - f)(x) = x - 8\)[/tex].
### Find [tex]\(m(x) = (g - j)(x)\)[/tex]:
Given:
- [tex]\( g(x) = x^2 + 6x + 5 \)[/tex]
- [tex]\( j(x) = -4x \)[/tex]
Step-by-step process:
1. Write the expression for [tex]\((g - j)(x)\)[/tex]:
[tex]\[ m(x) = (g - j)(x) = g(x) - j(x) = (x^2 + 6x + 5) - (-4x) \][/tex]
2. Distribute the subtraction to each term, noting that subtracting a negative is the same as adding:
[tex]\[ m(x) = x^2 + 6x + 5 + 4x \][/tex]
3. Combine like terms:
[tex]\[ x^2 + 6x + 4x + 5 = x^2 + 10x + 5 \][/tex]
So, [tex]\(m(x) = x^2 + 10x + 5\)[/tex].
### Evaluate [tex]\(m(3)\)[/tex]:
Given [tex]\(m(x) = x^2 + 10x + 5\)[/tex]:
Substitute [tex]\(x = 3\)[/tex] into the function:
[tex]\[ m(3) = (3)^2 + 10(3) + 5 \][/tex]
[tex]\[ m(3) = 9 + 30 + 5 \][/tex]
[tex]\[ m(3) = 44 \][/tex]
Therefore, [tex]\(m(3) = 44\)[/tex].
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.